ENTREPRENEURSHIP DAN PENDIDIKAN DALAM GEREJA - Tenny Tenny (Metanoia, 2020)
In the colonial era, the people of Indonesia had become slaves of the colonizers, which is three and a half centuries, both physically and mentally. In modern times and all digital now, it turns out there are still people who are still living pre-prosperous, due to notbeing financially literate and not aware of the opportunities that exist, meaning that they physically look independent, but mentally not necessarily independent, so they are not yet alive as humans should as a noble creation of God called to be pro active and productive. In this millennial era, the present and future generations must be able to fight for and manage abundant resources. Entrepreneurship education is one of the proactive and productive attitudes, thus creating an independent and prosperous life, from poverty to economic prosperity. Entrepreneur education is an educational concept that encourages students to be creative and innovative in working on existing opportunities. Entrepreneur education is an education that directs and equips students to be able to quickly respond to change and understand, and respond to the socio-economic needs of society today. The government should be willing to pay more attention and provide adequate funding so that the entrepreneurship education process can run and run effectively. Parents must provide entrepreneur education early for their children, Teachers must teach entrepreneurial spirit to their students, the community must be more active and intensive in monitoring the development of entrepreneurial education if they want the nation to progress, not only to become coolie nation by sending TKI/ TKW overseas, mostly as maids or manual laborers. A country that is rich in natural resources if supported by resources that have a high entrepreneurial spirit will become a prosperous country so that poverty will automatically decrease. Likewise the spirit of entrepreneurship must be owned by church members, so the church must prepare adequate entrepreneurship education to improve the welfare of church members who are still living underprivileged and change their paradigm for a life of giving and being a blessing, no longer living a burden and waiting for someone else's gift.